COLLABORATIVE GOVERNANCE PENYELENGGARAAN INFRASTRUKTUR JARINGAN UTILITAS DI KOTA TANGERANG - Sugara, Asep; Pratala, Esaka; Supriyadi, Yudi Nur; Syamsudin, AA Chaerul (Gapenas Publisher, 2025)
This study explores Collaborative Governance in the Management of Utility Network Infrastructure in Tangerang City, focusing on the interaction between local government and the private sector in managing utility networks. The research employs a qualitative approach, collecting data through in-depth interviews with key stakeholders, including the Public Works and Spatial Planning Agency (PUPR), the Regional Development Planning Agency, the Investment and One-Stop Integrated Services Agency, the Transportation Agency, the Civil Service Police Unit, and representatives from private sector utility providers. The findings indicate that Collaborative Governance in utility infrastructure management in Tangerang City faces several challenges, including lack of initial coordination, differences in regulatory interpretation, and difficulties in policy integration between agencies and the private sector. However, several strategies have been implemented to enhance cooperation, such as improving cross-sector communication, aligning regulations, and utilizing digital technology for planning and monitoring utility network infrastructure. The study concludes that the success of Collaborative Governance heavily depends on active stakeholder involvement, transparency in policymaking, and a shared commitment to sustaining utility infrastructure. Therefore, a more structured and participatory approach is needed in planning and implementation to create a more efficient, inclusive, and sustainable utility network system in Tangerang City.